2020
DOI: 10.3389/fnbot.2020.00003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Robotic Rehabilitation System With Muscle-to-Muscle Interface

Abstract: In this study, we developed a novel robotic system with a muscle-to-muscle interface to enhance rehabilitation of post-stroke patients. The developed robotic rehabilitation system was designed to provide patients with stage appropriate physical rehabilitation exercise and muscular stimulation. Unlike the position-based control of conventional bimanual robotic therapies, the developed system stimulates the activities of the target muscles, as well as the joint movements of the paretic limb. The robot-assisted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Functional electrical stimulation (FES) could stimulate muscles to produce joint movement, or to stimulate the lower limbs in motion to cooperate with exoskeleton. 81,82 The overall physical condition of patients with FES assisted training has been significantly improved: Hwan et al 83 combined robot assisted exercise with FES, the system can be operated in three different modes allowing both passive and active exercises, it can better protect the user from secondary injury. Ama et al 84 designed a dynamic hybrid exoskeleton called Kinesis that can effectively balance muscular and robotic actuation during walking.…”
Section: Resultsmentioning
confidence: 99%
“…Functional electrical stimulation (FES) could stimulate muscles to produce joint movement, or to stimulate the lower limbs in motion to cooperate with exoskeleton. 81,82 The overall physical condition of patients with FES assisted training has been significantly improved: Hwan et al 83 combined robot assisted exercise with FES, the system can be operated in three different modes allowing both passive and active exercises, it can better protect the user from secondary injury. Ama et al 84 designed a dynamic hybrid exoskeleton called Kinesis that can effectively balance muscular and robotic actuation during walking.…”
Section: Resultsmentioning
confidence: 99%
“…Volitional muscle activity can be measured using EMG by filtering out artifacts that appear when FES and EMG are applied to the same muscle. Several studies have suggested the use of calculation-based filters to remove artifacts ( Langzam et al, 2006 ; Erez et al, 2010 ; Bong et al, 2020 ). These studies investigated methods for suppressing large artifacts induced by FES.…”
Section: Coordination Control Of Pafo and Fesmentioning
confidence: 99%
“…EMG is conventionally used to measure the muscle activity. Many studies have employed EMG to trigger and control the motion of exoskeletons ( Frigo et al, 2000 ; Del-Ama et al, 2014 ; Bong et al, 2020 ; Yin et al, 2020 ). Del-Ama et al (2014) proposed an EMG-based control system that is capable of maintaining motion-tracking performance by compensating for muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robot yardımlı hareket ve paretik taraf kaslarındaki elektriksel uyarı, paretik ve etkilenmemiş taraflar arasındaki hareket ve kas aktivitelerinin online karşılaştırılmasıyla kontrol edilebilmektedir. Geliştirilen bu sistem ile rehabilitasyon egzersizi, hastanın inme sonrası motor toparlanma aşamasına bağlı olarak özelleştirilebilir ve modüle edilebilir (Bong et al, 2020;Lo et al, 2017).…”
Section: şEkil 3 Alt Ekstremite İçin Rehabilitasyon Robotuunclassified